Battling for Consumer's Positive Purchase Intention: A Comparative Study Between Two Psychological Techniques to Achieve Success and Sustainability for Digital Entrepreneurships - Dong, Dandan; Malik, Haider Ali; Liu, Yaoping; Elashkar, Elsayed Elsherbini; Shoukry, Alaa Mohamd; Khader, J. A. (Frontiers in Psychology, 2021)
This research focuses on students' online purchase intentions in Pakistan towards different products available for sale on numerous e-business websites. This study's main objective is to determine which methodology is better to enhance customer online purchase intention while improving perceived benefits and lowering perceived risks associated with any available online product and entrepreneurships. AMOS 24 has been used to deal with the mediation in study design with bootstrap methodology. The study was conducted on 250 students of different educational institutes in Pakistan using a simple random sampling technique. A finding of this study suggests that both methods positively impact online purchase intention of consumers and Sustainable digital economy. But social media advertisement is more effective through enhancing the perceived benefits of products. In contrast, product content factors are more effective by lowering the perceived risks associated with available online products. Keywords: Purchase intentions, online purchase intention, perceived risk, social media, e-business, entrepreneurship, Organizational Sustainability